English in civil aviation: problems and solutions to meet future workforce demands - Puteh, Fatimah (Penerbit UTM Press, 2009)
aviation in malaysia began before the First World War. Proper organisation of civil aviation commenced in 1948 with the creation of the Department of Civil Aviation. Since English was the official language at the time, it was used in aviation as well. eventually, as a contracting state of the international aviation Organisation (iCaO), the then malaya, elected to continue the use of english for both military and civil aviation domestically and internationally.